Experimental & Numerical Studies of Vertical Motion Acceleration Analysis in Helideck on a Catamaran Floating Crane - Eko Budi Djatmiko; Murdjito Murdjito; Yunan Setiawan Suwandono; Abdul Ghofur (International Journal of Offshore and Coastal Engineering, 2021)
This research discusses the operability of vertical acceleration in the helideck. The experiment was carried out at the Maneuvering and Ocean Engineering Basin (MOB) facility of the BPPT-ITS Hydrodynamics Technology Center. The model being tested is the catamaran type with a scale of 1:36 to the original scale. Experimental testing using random waves with a Pierson-maskowitz spectrum with Hs = 2.5 and Hs = 6.37 m. The helideck only performs surge sway and heave tests. Meanwhile, numerical analyzes the effects of regular waves at heading 00 450 900 1350 1800 and obtained RAO for Heave, Roll, Pitch movements. For the analysis of landing operability at Helideck using the Olson and Marine criteria, where the limit of wave height according to Olson is obtained, namely for the incoming wave direction of 00, 900,1800, it should not be done more than 3 meters of wave height, while for conditions 450 and 1350 should not be above 4 meters. . For the HCA category, the critical condition when the direction of the wave of 900 with a wave height of 2 meters. At an altitude of 4 meters is the limit of the wave direction 00 450 1350 1800.